The impact of pre-operative angiography on nephron-sparing surgery and outcome in wilms tumor arising from horseshoe kidney: case report and literature review - Zarfati, Angelo; Rollo, Giovanni; Cassanelli, Giulia; Grimaldi, Chiara; Persano, Giorgio; Natali, Gian Luigi; Serra, Annalisa; Madafferi, Silvia; Inserra, Alessandro; Martucci, Cristina; Crocoli, Alessandro (Frontiers in Surgery, 2025)
BackgroundThe horseshoe kidney (HSK) is a congenital renal anomaly characterized by the fusion of two distinct units, which are connected by a parenchymal bridge. HSK has a terminal vascular supply as a normal kidney. In the uncommon event that a Wilms Tumor (WT) (or Nephroblastoma) results from an HSK, Nephron-Sparing Surgery (NSS) is required. Since the anatomy expressed by HSK can vary substantially, an extensive preoperative evaluation of the vascularization is required to increase the likelihood of NSS and reduce complications. However, the role of pre-operative angiography (PORA) in this setting has not yet been defined. Our aim was to define the impact of PORA on NSS and its outcomes in WT arising from HSK.Case presentationWe presented a case of an 8-year-old girl with a WT in a HSK, for whom the PORA was safe and helpful in terms of NSS and surgical outcomes. Additionally, we performed a review of the literature regarding PORA's effects on the surgical and clinical outcomes of WT in patients with HSK.ConclusionPORA seemed potentially safe and useful in terms of NSS and complications. Despite its invasiveness, this interventional study may have a role in the extremely selected group of patients with WT arising from an HSK. Further studies are needed to validate our results.